Infection in the clinic of internal diseases - L I Dvoretsky; S V Yakovlev (Терапевтический архив, 2018)
In the modern clinic of internal diseases, the specific gravity of the infectious pathology, manifested by various clinical syndromes, is increasing. Infectious pathology is represented by diseases of the respiratory system, heart disease (infective endocarditis, cardioimplant infections, viral myocarditis), infectious arthropathies, extrahepatic manifestations of viral hepatitis, cytopenic syndromes, various manifestations of sepsis and some other conditions.In most cases, the diagnosis and management of such patients is the responsibility of the internist, who must be able to suspect the infection and carry out its verification. In the process of diagnostic search and management of patients, close interaction of the internist with a clinical microbiologist, clinical pharmacologist and other related specialists is necessary.